The Concept of Neuro- Linguistic Programming in Improving the Receptive Skills in English - Sunitha, S.; Jayanthy, A .Catherin; Kalaiyarasan, G.; Annalakshmi, N. (Rupkatha journal on interdisciplinary studies in humanities, 2021)
From the long years ago, education have been trying a proper way to improving the skills of English. Educators tried several methodologies in English to choose the better one. This paper brings out the effect of teaching Receptive skills by implementing NLP (Neuro- Linguistic Programming) in second language as English. Neuro- Linguistic Programming is one of the methods to catch up the English by giving focus on the brain anatomy. Brain anatomy can motive the creativity as well as the skills of using language. It also exist the role of Neuro Linguistic Programming in teaching the Receptive skills of English, which could make the students to improve the Receptive skills such as listening and reading. The study, in short, affirms that NLP strategies could be quite efficacious in making the students procure the skills that are indispensable in workplaces effortlessly. As it involves teaching a reading comprehension course by NLP concepts and techniques, the approach used in this study is experimental. In addition, the experimental method involves pre-and post-tests conducted before and after the course by the control group (40 students) and the experimental group (40 students). The students of the experimental community are chosen from the secondary school students. After the NLP experimentation, it was revealed from the study that there was a significant difference in the level of the experimental group in pre and post-test.